Arthroscopic suture fixation of comminuted tibial spine fractures-a prospective study - Shantanu Kumar; Sudhir Shyam Kushwaha; Shailendra Singh; Deepak kumar; Vinnet Sharma (International Journal of Medical Research and Review, 2016)
Introduction:Tibial spine fractures are common injuries and various techniques have been described for the fixation. The purpose of the article is to make familiar with thearthroscopic fixation of the anterior cruciate ligament bony avulsion injuries using non absorbable sutures and simple methods and instruments. Adequate reduction, anterior cruciate ligament integrity and regaining the bio-mechanics of the knee are the ultimate goal to be achieved failing which non union and malunion ensues. This technique has resulted in achieving excellent results and thus avoiding complications like joint laxity, flexion deformity&pain.Methods:Twenty one patients underwent arthroscopic suture fixation of the comminutedtibial spine fractures. Mean age of the patient was 24.28 years (range 16 to 38 years). All of the patients belonged to the Meyer type IV. The mean duration of follow up was 15.5 months with a minimum of one year follow-up.Results:All patients showed negative Lachman test except one having grade 1 positive lachman. No patient showed extension loss. 90.4 % (n=19) patients had an IKDC grade A while two patients belonged to grade B. All patients returned to their previous activity level.Conclusion:The above excellent results show that arthroscopic suture fixation of the comminutedtibial spine is promising and reliable technique to achieve the best biomechanics of the knee.